Coalition Politics in Central Eastern Europe Governing in Times of Crisis - Bergman, Torbjörn; Ilonszki, Gabriella; Hellström, Johan (Routledge Research in Comparative Politics, 2024)
This insightful book brings the study of coalitions and coalition governance in Central and Eastern European democracies up to date, with an analytical focus framed by difficult economic and social periods, such as the end of the economic crisis and the Coronavirus pandemic. The volume posits insights from a plethora of experts on party politics and coalition studies from their respective countries, with chapters on Bulgaria, Czechia, Estonia, Hungary, Latvia, Lithuania, Poland, Romania, Slovakia, and Slovenia. Embellished with illustrative tables and extensive datasets throughout, each chapter maps the developments of party system change, covering the coalition life cycle from the early 1990s until the end of 2021, and explores whether there has been transformation of the coalition, governance and dissolutions patterns due to heightened pressures. This book will be of key interest to scholars and students of coalition politics, representative democracy, governance, political parties, European Union politics, East and Central European politics, and comparative politics.